Evaluation of the HBV liver reservoir with fine needle aspirates - Barbara Testoni; Armando Andres Roca Suarez; Arianna Battisti; Marie-Laure Plissonnier; Marintha Heil; Thierry Fontanges; François Villeret; Yasmina Chouik; Massimo Levrero; Upkar Gill; Patrick Kennedy; Fabien Zoulim (JHEP Reports, 2023)
Background & Aims: Finite duration of treatment associated with HBsAg loss is the current goal for improved therapeutic approaches against chronic HBV infection, as it indicates elimination or durable inactivation of intrahepatic covalently closed circular DNA (cccDNA). To assist drug development, the definition of early predictive markers of HBsAg loss by assessing their value in reflecting intrahepatic cccDNA levels and transcriptional activity is essential. Fine needle aspirates (FNAs) have recently emerged as a less invasive alternative to core liver biopsy (CLB) and showed to be useful for investigating intrahepatic immune responses. The aim of this study was to optimise and validate the use of FNA vs. CLB to evaluate the intrahepatic viral reservoir. Methods: Paired FNA/CLB samples were obtained from patients with HBeAg+ chronic hepatitis (n = 4), HBeAg− chronic hepatitis (n = 4), and HBeAg− chronic infection (n = 1). One HBeAg+ patient was undergoing tenofovir treatment. HBV 3.5-kb RNA and cccDNA were quantified by droplet digital PCR. Results: cccDNA was quantifiable in all but one FNA/CLB pair, showing the highest levels in untreated HBeAg+ patients, except for the tenofovir-treated patient. Similarly, 3.5-kb RNA was detectable in all but one FNA sample and showed higher levels in HBeAg+ patients. When comparing cccDNA and 3.5-kb RNA quantification in FNA vs. CLB samples, no statistically significant differences were identified. Conclusions: These results demonstrate the possibility to quantify cccDNA and assess its transcriptional activity in patients with chronic hepatitis B by combining FNA and droplet digital PCR. This supports the use of FNA in clinical trials to evaluate the intrahepatic viral reservoir during the development of new antivirals and immunomodulatory agents. Impact and implications: Chronic hepatitis B infection is characterised by a complex interplay between immune responses and viral replication in the liver, which determines the long-term outcome of the disease. In this study, we show that fine needle aspiration of the liver, a less-invasive alternative to core biopsies, allows the assessment of the hepatic viral reservoir.